2015
DOI: 10.15171/joddd.2015.024
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Emergency Management of Traumatized Teeth among Schoolteachers in Mashhad, Iran

Abstract: Background and aims. Dental trauma is an important oral health problem in children that requires immediate and appropriate management for long term success. The aim of this study was to evaluate the knowledge of elementary school teachers about emergency management of traumatic dental injuries in children.Materials and methods. A total of 163 teachers from 21 elementary schools from Mashhad, Iran participated in this study. Data were collected using a two-part questionnaire comprised of questions regarding dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(33 reference statements)
3
3
0
Order By: Relevance
“…In this study, female students were predominant in both departments, however, among classroom education students, males were more than early childhood education division. This is similar to some other studies in which dental trauma and avulsion knowledge of preschool and classroom teachers were assessed 12,15,16,18,22,33 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In this study, female students were predominant in both departments, however, among classroom education students, males were more than early childhood education division. This is similar to some other studies in which dental trauma and avulsion knowledge of preschool and classroom teachers were assessed 12,15,16,18,22,33 .…”
Section: Discussionsupporting
confidence: 85%
“…37.2% of the students had low and 60.0% had moderate level of dental trauma knowledge. The most level is moderate, similar as Mehrabkhani et al 33 and Francisco et al 18 . It is thought that both department students had not sufficient knowledge about dental trauma and avulsion, and it is suggested that these information should be included in the scope of pregraduation education.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Lack of training on dental emergencies among school teachers is also found from other previously published studies. [8][9][10] In Malaysia, the Ministry of Health runs a continuous dental education under school dental programs where the dental team conducts various oral health promotion activities such as dental checkups and talk at school. Yet, little is known to which extent dental trauma topic is covered throughout the program.…”
Section: Discussionmentioning
confidence: 99%